Characterization and cost analysis of a modified silica gel-based adsorption desalination application. (15th December 2022) - Alsaman, Ahmed S.; Askalany, Ahmed A.; Ibrahim, E.M.M.; Farid, A.M.; Ali, Ehab S.; Ahmed, M. Salem
Abstract: This study aims to reduce adsorption desalinated water cost by innovative employing silica gel/CaCl2 composite and novel silica gel/(NH4 )2 CO3 activated materials. Raw silica gel (SG), which served as the host matrix, was acid-treated and impregnated with CaCl2 and (NH4 )2 CO3 . The prepared samples characteristics (XRD, N2 adsorption, water vapor adsorption) have been investigated and compared to the raw SG. A simulation model has been used to investigate the impact of the study samples on adsorption desalination (AD) system performance with and without heat recovery (HR). The study also includes a cost analysis of the AD water production system (using the tested materials) that uses solar energy or a waste heat source. The SG/CaCl2 achieved the highest water adsorption (0.95 kgH2O /kg) with a SDWP of 23.3 m 3 /ton per day, SCP 660 W/kg, and COP 0.71. With HR, the system could produce 35 m 3 /ton of SG/CaCl2 per day SDWP. The study concluded that the tested samples outperform the raw material as the total production cost of AD water using SG/CaCl2 has been reduced to approximately 37% using solar energy and 60% using waste heat as a regenerative heat source. Graphical abstract: Image 1 Highlights: Silica gel/CaCl2 is presented for adsorption desalination application. The silica gel/CaCl2 achieved water adsorption uptake of 0.95 kgH2O /kg. The maximum water production of 35 m 3 /ton per day was obtained. The water production cost of 0.767 $/m 3 . The adsorption desalinated water cost has been reduced by 60%.